IMPLEMENTASI PENERIMAAN PESERTA DIDIK BARU (PPDB) ONLINE DI DINAS PENDIDIKAN KOTA SURAKARTA - -, Rizlaili Istiqomah -; -, Kristiani -; -, Budi Wahyono - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
This study aims to determine 1) the implementation of online new student admission or Penerimaan Peserta Didik Baru (PPDB) online in Surakarta City, 2) supporting factors and inhibiting factors in the implementation of online new student admission or Penerimaan Peserta Didik Baru (PPDB) in Surakarta City, 3) the effectiveness of the implementation of new student admission or Penerimaan Peserta Didik Baru (PPDB) in Surakarta City. This research belongs to descriptive research with qualitative approach. The subjects of this study were Education Department of Surakarta, State and Private Junior High School and the community in Surakarta. Purposive sampling and snowball sampling were used as sampling techniques. Data collection techniques used in this research were observation, interview and documentation. Data triangulation and methodology triangulation were applied as techniques to test validity. Data analyzing techniques used was interactive model by Miles and Huberman that included data reduction, data display, and conclusion.The results showed that: 1) the implementation of online new student admission (PPDB) in Surakarta City employed zonation. In the implementation of online new student admission (PPDB) in Surakarta City, there were preparatory activities undertaken by Education Department and the schools. The implementation of online new student admission (PPDB) in Surakarta started with registration filling, server input, selection, selected result announcement and re-registration activities, 2) Supporting factors included adequate resources and the availability of adequate facilities and infrastructure. Inhibiting factors included: insufficient time, some parents or society that might not comprehend zonation, and lack of socialization/information to the society. 3) The effectiveness of the implementation of online new student admission (PPDB) in Surakarta was effective in terms of some indicators such as purpose achievement, resources availability, and acceptable internal process, constituent satisfaction of the implementation of acceptance of online new student admission (PPDB) in Surakarta. However in the implementation of online new student admission (PPDB) still there are problems in the community.